La question du préjudice en matière de retard à transmettre un avis de sinistre et l’assurance de responsabilité - Borgia, Denis (Assurances)

(untitled) (HEC Montréal, 1987)
In this article, Mr. Denis Borgia reminds us of the importance for the insured of advising the insurer as soon as possible of a claim, so that the former cannot invoke the fact that he was not informed within a reasonable period of time. A number of our collaborators have already discussed this question, but Mr. Borgia presents an excellent study of the matter and of jurisprudence related thereto.